Socio-Economic Empowerment of The Community Through Islamic Boarding School - Sihabudin; Aminudin; Alisah Qothrun Nada Rahmah; Masdar Hilmy (Jurnal Abdimas Cendekiawan Indonesia, 2025)
This study examines the transformative role of Pondok Pesantren Darussalam Kunir in fostering socio-economic development within its surrounding community. By implementing empowerment programs that integrate students (santri) and local residents, the pesantren not only serves as an educational institution but also as a catalyst for sustainable economic growth. Through job creation, vocational training, and cooperative development, the pesantren enhances local livelihoods while fostering self-reliance. Key initiatives include hiring local labor in agriculture, construction, and livestock management, as well as operating cooperatives that supply essential goods to both the pesantren and the broader community. Moreover, entrepreneurial training has empowered local residents to establish and sustain small businesses, reducing economic dependency and promoting financial resilience. The findings reveal a significant socio-economic impact, demonstrating how pesantren-based initiatives can serve as scalable models for community-driven development. Strengthening partnerships with government agencies and private sectors could further amplify these impacts, ensuring long-term economic sustainability. This study contributes to the discourse on the role of Islamic educational institutions in community empowerment, offering insights for policymakers and development practitioners seeking to integrate religious institutions into broader socio-economic frameworks.